CCR2 Contributes to F4/80+ Cells Migration Along Intramembranous Bone Healing in Maxilla, but Its Deficiency Does Not Critically Affect the Healing Outcome - Biguetti, Claudia Cristina; Vieira, Andreia Espindola; Cavalla, Franco; Fonseca, Angélica Cristina; Colavite, Priscila Maria; Silva, Renato Menezes; Trombone, Ana Paula Favaro; Garlet, Gustavo Pompermaier (Frontiers in Immunology, 2018)
Bone healing depends of a transient inflammatory response, involving selective migration of leukocytes under the control of chemokine system. CCR2 has been regarded as an essential receptor for macrophage recruitment to inflammation and healing sites, but its role in the intramembranous bone healing on craniofacial region remains unknown. Therefore, we investigated the role of CCR2 on macrophages migration and its consequences to the intramembranous healing outcome. C57BL/6 WT and CCR2KO mice were subjected to upper right incisor extraction, followed by micro–computed tomography, histological, immunological and molecular analysis along experimental periods. CCR2 was associated with macrophage influx to the intramembranous bone healing in WT mice, and CCR2+ cells presented a kinetics similar to F4/80+ and CCR5+ cells. In contrast, F4/80+ and CCR5+ cells were significantly reduced in CCR2KO mice. The absence of CCR2 did not cause major microscopic changes in healing parameters, while molecular analysis demonstrated differential genes expression of several molecules between CCR2KO and WT mice. The mRNA expression of TGFB1, RUNX2 and MSCs markers (CXCL12, CD106, OCT4, NANOG and CD146) were decreased in CCR2KO mice, while IL6, CXCR1, RANKL and ECM markers (MMP1, 2, 9 and Col1a2) were significantly increased in different periods. Finally, immunofluorescence and FACS revealed that F4/80+ cells are positive for both CCR2 and CCR5, suggesting that CCR5 may account for the remaining migration of the F4/80+ cells in CCR2KO mice. In summary, these results indicate that CCR2+ cells play a primary role in macrophages migration along healing in intramembranous bones, but its deficiency does not critically impact healing outcome.